Unpacking the digital competence challenge in vocational education: A case from Indonesia - Sherly Rahmawati; Sarah Prestridge; Ade Gafar Abdullah; Isma Widiaty (Social Sciences and Humanities Open, 2025)
The rapid advancement of technology in the workplace requires workers to be highly skilled in the industry. However, many vocational educators, who are essential in preparing graduates for these roles, exhibit low levels of digital competence. This deficiency impacts students' competence in technology in their future careers. Therefore, this study aims to identify the factors contributing to vocational educators' low level of digital competence. Through a focus group discussion (FGD), this study describes the factors behind vocational educators' low digital competence in Indonesia to find deeper insights of their experience. A qualitative thematic analysis approach was used for the data analysis through an axial code method. Data were gathered through a focus group discussion (FGD) with ten purposefully selected teachers representing a range of teaching experiences and subject specialties. The findings indicated that teachers in vocational education exhibit low levels of digital competence due to several factors, categorized into two main groups: External factors that include limited access to the internet and hardware, an unsupportive online community, time constraints, and insufficient government training; and internal factors that stem from senior teachers' beliefs and a lack of confidence compared to younger teachers' abilities. New insights into this field are provided which are instrumental for evaluating policies related to the development and training of teachers’ digital competence.